(untitled) (Journal of Veterinary Medicine and Animal Production, 2023)
Abstract The in vitro preimplantation developmental potential and the quality of blastocysts produced by somatic cell nuclear transfer (SCNT) were examined compared to in vitro fertilized embryos (IVF). SCNT embryos were reconstituted from small and medium size donor cumulus cells synchronized at the G0-G1 cell stage by serum starvation and electrically fused to metaphase II arrested enucleated oocytes. The cell cycle phase of the donor cells was confirmed at the G0-G1 by flow cytometric analysis. In vitro fertilized embryos were produced by incubating the mature cumulus oocyte complexes with motile spermatozoa for 18 h at 39°C under a humidified air with 5% CO2. Presumptive zygotes were cultured to the blastocyst stage in modified synthetic oviduct fluid medium. The cleavage rate and the development to blastocyst were the same for both types of embryo. SCNT blastocysts were morphologically similar to the IVF ones without significant difference in their cell number.